The Doctor's Dilemma: Oranges or Apples? - Norman L Jones (Canadian Respiratory Journal)
George Bernard Shaw's famous play, Doctor's Dilemma (1), is one of the attractions at the Shaw Festival this year, and recently we went to see it on a beautiful Niagara summer day, followed by a picnic beside Ball's Falls. Several weeks earlier, I had decided to read the play, with its 80-page "Preface on Doctors", and was prepared for an anticlimactic experience on the day. However, the production was a delight and I gained additional insights from the live performance.